Center-Pivot-Irrigated Soybean Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R.; O'Brien, Daniel M.; Olson, Brian L.S. (My University, 2007)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated soybean production in western Kansas.
MF586_2007_10
Keywords: MF586; Economics; Crops; MF